Difficulties in the application of modern trends in physics in middle schools of the province of Baghdad, from the perspective of teachers of physics (Journal Of Educational and Psychological Researches, 2017)
The goal of current research is to identify the difficulties in the application of modern physics in the middle schools of the province of Baghdad schools from the perspective of teachers of physics trends, sample search of (127) teachers, Karkh Third Directorate, and use Researcher questionnaire data collection tool after applying it to teachers who have experience (5) years and more after confirmation of the validity and reliability of the scale (the tool) researcher has used the averages for the purpose of interpreting the results. the results showed that the difficulties have been in the order following: (difficulties related educational environment of modern trends of teaching, curriculum-related difficulties, difficulties related to students, difficulties related to the teacher) as the researcher presented a set of recommendations and proposals